Control of Unmanned Underwater Vehicle as a Member of Vehicles Team Performing a Given Task - Zak, Andrzej (Transactions on Maritime Science, 2019)
The article presents the control system of a single underwater vehicle which is a member of the underwater vehicles team. The application of the multi-agent system concept for modelling and controlling a team of homogeneous underwater vehicles is discussed. Issues relating to cooperation actions in the team of underwater vehicles are described and solved using the theory of games and vector quality index. The process of negotiations between the vehicles is modelled as a multiplayer cooperative game. Finally, the water region search tasks performed by a team of cooperating underwater vehicles are presented and discussed taking into account possible vehicle failures happening during task realization.